Friedrich István szerepe Keresztény Nemzeti Egyesülés Pártjának létrejöttében és felbomlásában = Stephen Friedrich role in the creation and dissolution of Christian National United Party - Köpfler, Balázs (Közép-Európai Közlemények, 2017)
By the end of the first World War Hungary, was in terible situation. A significant part of the country was occupied, there was not enough food and coal; and the Entente didn’t recognize the Hungarian leadership. Under these conditions Stephen Friedrich (Hungarian Prime Minister, August 7th, 1919 to November 24th, 1919) struggled to maintain his positon. One of his strategies was the National Christian Movement. Like other political parties, national christians and christian-socialist intended to merge political parties in order to avoid dissipation. On day before October 23rd, 1919 an envoy of the Entent arrieved Budapest, where they established the Christian National United Party. The leader of the party was Friedich. He became defense minister in Charles Huszar’s cabinet, from November 25th, 1919 to March 14th, 1920. In this positon he got into many fi ghts. He was weakened mostly because he became aff ected by Tisza case. Hungary had its fi rst overall secret and equivalent voting on January 25-26th, 1920. Friedrch was very successful. He overcame Alexander Wekerle (who also was prime minister). After that his situation worsened. His supporters couldn’t beat their opponents. Friedrich and his follewers became antagonistic with every other group. They left the CNUP on April 23rd, 1920, and became the strongest opposition party.